PENGEMBANGAN MODUL AJAR BERBASIS PROJECT BASED LEARNING TERHADAP KEMAMPUAN BERPIKIR KREATIF SISWA: Development of Project-Based Learning Modules to Enhance Students' Creative Thinking Skills - Prihartini (UNIVERSITAS HAMZANWADI, 2026)
This study aims to develop a Project-Based Learning-based teaching module whose validity, practicality, and effectiveness in enhancing students’ creative thinking skills have been tested. The research and development utilized the Borg and Gall model, which was carried out through seven development stages: 1. Initial information gathering, 2. Planning, 3. Development of the initial product format, 4. Preliminary testing, 5. Product revision, 6. Small-scale testing, 7. Final product revision. The research participants in this study were subject matter experts, design experts, teachers, and students from MA NW Kotaraja, as well as students from SMAN 1 Aikmel. Data were collected using questionnaires and analyzed using quantitative descriptive analysis. Based on the results of the data analysis and discussion, it was concluded that the project-based learning teaching modules designed to enhance students’ creative thinking skills are highly valid and effective